Temporal trend, distribution and spatial autocorrelation of leprosy in Brazil: ecological study, 2011 to 2021 - Lucas Vinícius de Lima; Gabriel Pavinati; Isadora Gabriella Pascholotto Silva; Débora Regina de Oliveira Moura; Nelly Lopes de Moraes Gil; Gabriela Tavares Magnabosco (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: To characterize the temporal trend and spatial behavior of leprosy in Brazil, from 2011 to 2021. Methods: This is an ecological study, with data from the Notifiable Diseases Information System, obtained in June 2022. The annual detection rate of new leprosy cases per 100 thousand inhabitants was calculated. To estimate the trend of the 2011-2019 and 2011-2021 series, the polynomial regression model was used, testing first-, second-, and third-order polynomials. For spatiality, natural breaks were used and, later, the univariate global and local Moran's indexes. A significance level of 5% was adopted and the analyses were performed using SPSS®, GeoDa®, and QGIS® software. Results: The findings indicated an upward trend in the incidence of leprosy in Brazilian regions and in 20 federative units between 2011 and 2019. However, there was a decrease in most of the country when considering the COVID-19 pandemic years. Spatiality showed that the highest detection rates throughout the period were observed in the North, Midwest, and Northeast regions, with high-risk clusters, and the lowest detection rates in the South and Southeast regions, with low-risk clusters. Conclusion: The leprosy detection rate showed an upward trend in Brazil between 2011 and 2019, with greater spatial concentration in the North, Northeast, and Midwest regions. Nevertheless, the study raises an alert for the programmatic sustainability of leprosy control in Brazil, considering the drop in the COVID-19 pandemic, presumably due to the influence of the reorganization of the development of initiatives and provision of services in face of COVID-19.